STUDY OF CARRYING CAPACITY OF A CORRUGATED METAL CONSTRUCTION BY CRITERION OF YIELD HINGE DEVELOPMENT - Luchko, Y. Y.; Kovalchuk, V. V.; Nabochenko, O. S. (Science and Transport Progress, 2015)
Purpose. This research is aimed to: 1) calculation of equivalent forces caused by rolling stock in winter and summer seasons at different parameters of the irregularities of railway track; 2) research of bearing capacity of corrugated metal constructions (CMC) in terms of development of plastic hinge in the top of the metal pipe due to irreversible residual deformation of the vertical and horizontal diameters of the pipe. Methodology. The calculation of equivalent forces is carried out according to the method of calculating the railway track on strength and stability. Further a mathematical algorithm was developed in the software environment of Mathcad 14, with which the calculations were made about the formation of a plastic hinge at the top of the pipe for different values of the irregularities of the railway track and the degree of compaction of soil backfill. In these studies, the calculations were carried out at the design value of the compaction degree of soil backfill and magnitude of dynamic loading on railway rolling stock. Findings. Analysis of multivariate calculations of testing the condition of occurrence of plastic hinge at the top of the pipe arch has revealed that the first plastic hinge, which occurs in the set of CMC is revealed only when there is a simultaneous unfavorable influence of two factors (causes). These are the factors: the assumption of the development of the track irregularities out of the allowable values without the implementation of measures to eliminate or limit the speed of trains (the first cause); reduction of compaction of soil backfill below the 90 % (the second cause). In case of absence of one of the causes the origin of the plastic hinge will not happen. Originality. It was the first time, when the bearing capacity of corrugated metal construction with large diameter (more than 6 m) with account of factors complex: the degree of compaction of soil backfill, the magnitude of the dynamic loads from rolling stock by the criterion of plastic hinge development in the metal pipe when the occurrence of residual deformations of the vertical and horizontal diameters of the CMC was investigated. Practical value. The obtained results of the bearing capacity of corrugated metal constructions (like horizontal ellipse of cross-section) can be used by engineers of Bridge building stations of Ukrzaliznytsia, Ukravtodor and design organizations, which are engaged in the design of corrugated metal constructions with a diameter of more than 6 m.